Examples with solutions for Multiplication of Powers: Variable in the base of the power

Exercise #1

a3×a4= a^3\times a^4=

Video Solution

Step-by-Step Solution

Here, we will need to calculate a multiplication between terms with identical bases, therefore we will use the appropriate power property:

bmbn=bm+n b^m\cdot b^n=b^{m+n} Note that this property can only be used to calculate the multiplication between terms with identical bases,

We apply it to the problem:

a3a4=a3+4=a7 a^3\cdot a^4=a^{3+4}=a^7 Therefore, the correct answer is option b.

Answer

a7 a^7

Exercise #2

x2×x5= x^2\times x^5=

Video Solution

Step-by-Step Solution

Here we will have to to multiply terms with identical bases, therefore we use the appropriate power property:

bmbn=bm+n b^m\cdot b^n=b^{m+n} Note that this property can only be used to calculate the multiplication between terms with identical bases,

From now on we no longer write the multiplication sign, but use the accepted form of writing in which placing terms next to each other means multiplication.

We apply it in the problem:

x2x5=x2+5=x7 x^2x^5=x^{2+5}=x^7 Therefore, the correct answer is D.

Answer

x7 x^7

Exercise #3

Determine which of the following options is equal to the given expression?

a4a5 a^4\cdot a^5

Video Solution

Step-by-Step Solution

We will apply the law of exponents:

aman=am+n a^m\cdot a^n=a^{^{m+n}}

This means that when multiplying identical numbers raised to any power (meaning - identical bases raised to not necessarily identical powers), we can maintain the same base and simply add the exponents of the numbers,
Let's apply this law to the problem:

a4a5=a4+5=a9 a^4\cdot a^5=a^{4+5}=a^9

Something important to remember is that this solution can also be explained verbally. Raising to a power effectively means multiplying the number (base) by itself as many times as the exponent indicates. Therefore multiplying a a by itself 4 times and multiplying the result by the result of multiplying a a by itself 5 times is like multiplying a a by itself 9 times, meaning multiplication between identical numbers (identical bases) raised to powers, not necessarily identical, can be calculated by keeping the same base (same number) and adding the exponents together.

Answer

a9 a^9

Exercise #4

Reduce the following equation:

t7×t2= t^7\times t^2=

Video Solution

Step-by-Step Solution

To solve the problem of simplifying t7×t2 t^7 \times t^2 , we follow these steps:

  • Step 1: Identify the base and the exponents. Here, the base is t t , the first exponent is 7, and the second exponent is 2.
  • Step 2: Apply the exponent rule for multiplying powers with the same base, which states am×an=am+n a^m \times a^n = a^{m+n} .
  • Step 3: Add the exponents: 7+2=9 7 + 2 = 9 .
  • Step 4: Write the simplified expression: t9 t^9 .

Therefore, after applying the exponent rule, the simplified form of the expression is t9 t^9 .

The correct choice among the given options is not specifically listed, but the simplification corresponds to t7+2 t^{7+2} before explicitly adding to get t9 t^9 .

Answer

t7+2 t^{7+2}

Exercise #5

Reduce the following equation:

a2×a3×a4= a^2\times a^3\times a^4=

Video Solution

Step-by-Step Solution

To solve the problem of simplifying a2×a3×a4 a^2 \times a^3 \times a^4 , we apply the exponent rule for multiplying powers with the same base.

This rule states that to multiply powers with the same base, we add their exponents:

am×an=am+n a^m \times a^n = a^{m+n}

Applying this rule to the problem at hand:

  • The given expression is a2×a3×a4 a^2 \times a^3 \times a^4

  • We recognize that all parts have the same base, so we can add the exponents together: 2+3+4 2 + 3 + 4 .

  • Therefore, we simplify the expression to a2+3+4 a^{2+3+4} .

This matches with choice 4, a2+3+4 a^{2+3+4} .

Answer

a2+3+4 a^{2+3+4}

Exercise #6

Reduce the following equation:

y9×y2×y3= y^9\times y^2\times y^3=

Video Solution

Step-by-Step Solution

To solve the problem of simplifying the expression y9×y2×y3 y^9 \times y^2 \times y^3 , we will follow these steps:

First, recognize that the expression entails powers of the same base y y , and we can use the rule for multiplying powers with the same base. This rule states that when multiplying like bases, we add the exponents. Mathematically, this can be expressed as:

  • Step 1: Identify the base y y and the exponents 9 9 , 2 2 , and 3 3 .
  • Step 2: Apply the rule for multiplication of powers y9×y2×y3=y9+2+3 y^9 \times y^2 \times y^3 = y^{9+2+3} .
  • Step 3: Calculate the sum of the exponents: 9+2+3=14 9 + 2 + 3 = 14 .
  • Step 4: Simplify the expression to yield the solution, y14 y^{14} .

In reviewing the answer choices:

  • Choice 1: y9+2+3 y^{9+2+3} represents the fully simplified expression, which agrees with our solution.
  • Choice 2: y9+2×y3 y^{9+2} \times y^3 and choice 3: y9×y2+3 y^9 \times y^{2+3} still maintain some intermediate steps of simplification. Yet, both can eventually be simplified further to y14 y^{14} .

Therefore, all expressions represent correct approaches or intermediates toward achieving the correct final form. Thus, All answers are correct.

Answer

All answers are correct

Exercise #7

Reduce the following equation:

a2×a3= a^2\times a^3=

Video Solution

Step-by-Step Solution

To solve the given problem, we need to simplify the expression a2×a3 a^2 \times a^3 using the rules of exponents.

We use the rule for multiplying powers with the same base, which states:

  • If you have am×an a^m \times a^n , the result is am+n a^{m+n} .

Let's apply this rule to the given expression:

a2×a3=a2+3 a^2 \times a^3 = a^{2+3}

Simplifying the exponents, we get:

a2+3=a5 a^{2+3} = a^5

In the context of choosing from the given options, the answer corresponding to the application of the multiplication rule before final simplification is:

a2+3 a^{2+3}

Answer

a2+3 a^{2+3}

Exercise #8

Reduce the following equation:

b4×b5= b^4\times b^5=

Video Solution

Step-by-Step Solution

To solve this problem, we need to simplify the expression using the rules of exponents:

  • Step 1: Recognize the base b b is the same for both terms in the multiplication.

  • Step 2: Apply the exponent multiplication rule: add the exponents of like bases. Thus, b4×b5=b4+5 b^4 \times b^5 = b^{4+5} .

The correct answer to the problem isb4+5 b^{4+5} .

Answer

b4+5 b^{4+5}

Exercise #9

Reduce the following equation:

x8×x7×x10= x^8\times x^7\times x^{10}=

Video Solution

Step-by-Step Solution

To solve this problem, follow these steps:

  • Step 1: Identify the exponents in the expression x8×x7×x10 x^8 \times x^7 \times x^{10} . They are 8, 7, and 10.
  • Step 2: Apply the multiplication rule for exponents, which states am×an=am+n a^m \times a^n = a^{m+n} .
    Here, it becomes: x8×x7×x10=x8+7+10 x^8 \times x^7 \times x^{10} = x^{8+7+10} .
  • Step 3: Simplify the expression by adding the exponents together:

After performing the addition, 8+7+10=25 8 + 7 + 10 = 25 .

Thus, the reduced form of the equation is x25 x^{25} .

Therefore, the final answer is x25 x^{25} .

Answer

x25 x^{25}

Exercise #10

Reduce the following equation:

y2y3y6= y^2\cdot y^3\cdot y^6=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the exponents in the expression y2y3y6 y^2 \cdot y^3 \cdot y^6 .

  • Step 2: Apply the exponent rule by adding the exponents together.

  • Step 3: Simplify the combined exponents to find the final expression.

Now, let's work through each step:

Step 1: The exponents in the expression are 2, 3, and 6.

Step 2: According to the multiplication rule for powers with the same base, we have y2y3y6=y2+3+6 y^2 \cdot y^3 \cdot y^6 = y^{2+3+6} .

Step 3: Calculate the sum of the exponents: 2+3+6=11 2 + 3 + 6 = 11 .

Therefore, the simplified expression is y11 y^{11} .

Given the choices, the correct answers, by these computations, correspond to:

  • y11 y^{11}

  • y2+3+6 y^{2+3+6}

Hence, the correct answer to the problem is B+C are correct.

Answer

B+C are correct

Exercise #11

Reduce the following equation:

b9×b4×b5= b^9\times b^4\times b^5=

Video Solution

Step-by-Step Solution

To reduce the equation b9×b4×b5 b^9 \times b^4 \times b^5 , follow these steps:

  • Step 1: Identify the exponents present: 99, 44, and 55.
  • Step 2: Apply the exponent multiplication rule: Since the bases are the same, add the exponents: 9+4+5=189 + 4 + 5 = 18.
  • Step 3: Write the expression in its simplified form with the new exponent: b18 b^{18} .

Therefore, the simplified form of the expression is b18 b^{18} .

Answer

b18 b^{18}

Exercise #12

Reduce the following equation:

t6×t7= t^6\times t^7=

Video Solution

Step-by-Step Solution

To solve this problem, we'll follow these steps:

  • Step 1: Identify the base and the exponents from the given expression.
  • Step 2: Apply the rule for multiplying powers with the same base.
  • Step 3: Perform the addition to simplify the exponents.

Now, let's work through each step:
Step 1: The expression given is t6×t7 t^6 \times t^7 . The base here is t t , and the exponents are 6 and 7.

Step 2: According to the rule for multiplying exponents with the same base, we add the exponents. Therefore, the expression becomes:
t6×t7=t6+7 t^6 \times t^7 = t^{6+7} .

Step 3: Simplify the expression by adding the exponents:
6+7=13 6 + 7 = 13 .

Therefore, the simplified expression is t13 t^{13} .

The correct choice given is: t13 t^{13} , which is choice 2.

Answer

t13 t^{13}

Exercise #13

Expand the following equation:

a3+5= a^{3+5}=

Video Solution

Step-by-Step Solution

To solve this problem, we begin by rewriting the expression that incorporates exponent rules. The expression given is a3+5 a^{3+5} . According to the rule of exponents, when you have a base raised to a power that is a sum, am+n=am×an a^{m+n} = a^m \times a^n .

Let's apply this rule:

  • Write the exponent as a sum: 3+5 3 + 5 .
  • Apply the exponent rule: a3+5 a^{3+5} becomes a3×a5 a^3 \times a^5 .

Thus, the expanded form of a3+5 a^{3+5} using the rule of exponents is a3×a5 a^3 \times a^5 .

Finally, comparing with the provided options, choice 1 ( a3×a5 a^3 \times a^5 ) is the correct one, as it correctly uses the exponent rule.

Therefore, the solution to the problem is a3×a5 a^3\times a^5 .

Answer

a3×a5 a^3\times a^5

Exercise #14

Reduce the following equation:

a3x×ab×ab= a^{-3x}\times a^b\times a^b=

Video Solution

Step-by-Step Solution

To reduce the given equation a3x×ab×ab a^{-3x} \times a^b \times a^b , we will use the multiplication of powers rule for exponents, which states that if you multiply powers with the same base, you add the exponents.

Let's follow the steps:

  • Step 1: Identify that all terms share the same base, a a .

  • Step 2: Apply the rule: a3x×ab×ab=a3x+b+b a^{-3x} \times a^b \times a^b = a^{-3x + b + b} .

  • Step 3: Simplify the exponents by adding them: 3x+b+b=3x+2b -3x + b + b = -3x + 2b .

Therefore, the reduced form of the equation is a3x+2b a^{-3x + 2b} .

Answer

a3x+2b a^{-3x+2b}

Exercise #15

Simplify the expression:

a3a2b4b5= a^3\cdot a^2\cdot b^4\cdot b^5=

Video Solution

Step-by-Step Solution

In the exercise of multiplying powers, we will add up all the powers of the same product, in this case the terms a, b

We use the formula:

an×am=an+m a^n\times a^m=a^{n+m}

We are going to focus on the term a:

a3×a2=a3+2=a5 a^3\times a^2=a^{3+2}=a^5

We are going to focus on the term b:

b4×b5=b4+5=b9 b^4\times b^5=b^{4+5}=b^9

Therefore, the exercise that will be obtained after simplification is:

a5×b9 a^5\times b^9

Answer

a5b9 a^5\cdot b^9

Exercise #16

k2t4k6t2= k^2\cdot t^4\cdot k^6\cdot t^2=

Video Solution

Step-by-Step Solution

Using the power property to multiply terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n} It is important to note that this law is only valid for terms with identical bases,

We notice that in the problem there are two types of terms. First, for the sake of order, we will use the substitution property to rearrange the expression so that the two terms with the same base are grouped together. The, we will proceed to solve:

k2t4k6t2=k2k6t4t2 k^2t^4k^6t^2=k^2k^6t^4t^2 Next, we apply the power property to each different type of term separately,

k2k6t4t2=k2+6t4+2=k8t6 k^2k^6t^4t^2=k^{2+6}t^{4+2}=k^8t^6 We apply the property separately - for the terms whose bases arek k and for the terms whose bases aret t We add the powers in the exponent when we multiply all the terms with the same base.

The correct answer then is option b.

Answer

k8t6 k^8\cdot t^6

Exercise #17

ababa2 a\cdot b\cdot a\cdot b\cdot a^2

Video Solution

Step-by-Step Solution

We use the power property to multiply terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n} It is important to note that this property is only valid for terms with identical bases,

We return to the problem

We notice that in the problem there are two types of terms with different bases. First, for the sake of order, we will use the substitution property of multiplication to rearrange the expression so that the two terms with the same base are grouped together. Then, we will proceed to work:

ababa2=aaa2bb a\cdot b\operatorname{\cdot}a\operatorname{\cdot}b\operatorname{\cdot}a^2=a\cdot a\cdot a^2\cdot b\cdot b Next, we apply the power property for each type of term separately,

aaa2bb=a1+1+2b1+1=a4b2 a\cdot a\cdot a^2\cdot b\cdot b=a^{1+1+2}\cdot b^{1+1}=a^4\cdot b^2

We apply the power property separately - for the terms whose bases area a and then for the terms whose bases areb b and we add the exponents and simplify the terms.

Therefore, the correct answer is option c.

Note:

We use the fact that:

a=a1 a=a^1 and the same for b b .

Answer

a4b2 a^4\cdot b^2

Exercise #18

Simplify the following expression:

c1d6d2c3c2= c^{-1}\cdot d^6\cdot d^{-2}\cdot c^3\cdot c^2=

Video Solution

Step-by-Step Solution

Apply the power rule for multiplying terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n}

Note that this rule is valid only for terms with identical bases,

Here in the problem there are also terms with negative exponents, but this doesn't pose an issue regarding the use of the aforementioned power rule. In fact, this power rule is valid in all cases for numerical terms with different powers, including negative powers, rational number powers, and even irrational number powers, etc.

Let's return to the problem,

Note that there are two types of terms in the problem that differ from each other with different bases. First, we'll apply the commutative law of multiplication to arrange the expression so that all terms with the same base are adjacent, let's get to work:

c1d6d2c3c2=c1c3c2d6d2 c^{-1}\cdot d^6\cdot d^{-2}\cdot c^3\cdot c^2=c^{-1}\cdot c^3\cdot c^2\cdot d^6\cdot d^{-2}

Then we'll proceed to apply the aforementioned power rule separately to each different type of term,

c1c3c2d6d2=c1+3+2d6+(2)=c1+3+2d62=c4d4 c^{-1}\cdot c^3\cdot c^2\cdot d^6\cdot d^{-2}=c^{-1+3+2}\cdot d^{6+(-2)}=c^{-1+3+2}\cdot d^{6-2}=c^4\cdot d^4

To summarise we applied the above rule separately - for terms with base c c and for terms with base d d and then combined the powers in the exponent when we grouped all terms with the same base together.

Therefore, the correct answer is B.

Answer

c4d4 c^4\cdot d^4

Exercise #19

E6F4E0F7E= E^6\cdot F^{-4}\cdot E^0\cdot F^7\cdot E=

Video Solution

Step-by-Step Solution

We use the power property to multiply terms with identical bases:

aman=am+n a^m\cdot a^n=a^{m+n} It should be noted that this property is only valid for terms with identical bases,

We return to the problem

We notice that in the problem there are two types of terms with different bases. First, for the sake of order, we will use the substitution property of multiplication to rearrange the expression so that the two terms with the same base are grouped together. Then, we will proceed to work:

E6F4E0F7E=E6E0EF4F7 E^6\cdot F^{-4}\cdot E^0\cdot F^7\cdot E=E^6\cdot E^0\cdot E\cdot F^{-4}\cdot F^7 Next, we apply the power property for each type of term separately,

E6E0EF4F7=E6+0+1F4+7=E7F3 E^6\cdot E^0\cdot E\cdot F^{-4}\cdot F^7=E^{6+0+1}\cdot F^{-4+7}=E^7\cdot F^3

We apply the power property separately - for the terms whose bases areE E and for the terms whose bases areF F and we add the exponents and simplify the terms with the same base.

The correct answer is then option d.

Note:

We use the fact that:

E=E1 E=E^1 .

Answer

E7F3 E^7\cdot F^3

Exercise #20

Reduce the following equation:

b6×b3×b5= b^6\times b^3\times b^5=

Video Solution

Answer

b6+3+5 b^{6+3+5}